Effect Covid-19: Loyalty of Prospective Umrah Pilgrims to Umrah and Hajj Travel Companies - Ifah Finatri; Maat Pono; Jusni Jusni (Magister Management, Hasanuddin University, 2020)
This study aims to determine the extent of the loyalty of prospective pilgrims (costumer) to travel Umrah and Hajj in Makassar using price as an independent variable and trust as a mediating variable. This research is mixed-method research using questionnaires to 30 respondents and FGD in Meida Wisata company as one of the Umrah and Hajj travel companies in Makassar. Based on the results of data analysis, it is found that the price offered by PT. Meida Wisata has a negative but not significant impact on the loyalty of pilgrims, but the current price will have a significant positive effect on the loyalty of pilgrims and registrants if mediated by the variable of trust. The Covid-19 pandemic that occurred at this time did not reduce the enthusiasm of Umrah tourism consumers to continue to wait for the announcement from Saudi Arabia to receive Umrah pilgrims from Indonesia again and hope that the Covid-19 outbreak will soon end so that they can carry out Umrah through PT. Meida Wisata. There are still limitations in this study that can be continued by other researchers by increasing the number of respondents to get more general information.